PRESERVATION OF UANG ASAP TRADITION IN MELAYU WEDDING: MAQĀSID SHARI'AH PERSPECTIVE - Nofri Andy.N; Siti Humairah (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2022)
This article is the result of a qualitative field research. This research is a legal sociology research. This article discusses determination of “Uang Asap” in the Malay wedding tradition. The researcher analyzed the research data using the maqasid shariah theory. The location of this research is in Nusapati Village, Sungai Pinyuh District, Mempawah Regency, West Kalimantan. The findings of this study are that in the view of maqasid sharia, the determination of smoked money is included in the category of tahsiniyat (tertiary) benefit. Field data shows that the giving of smoked money is a general tradition, in the sense that it applies to everyone of the Malay ethnicity, especially in Nusapati Village, Sungai Pinyuh District, Mempawah Regency, West Kalimantan. Although the giving of smoked money is not explicitly regulated in maqasid sharia, the giving of smoked money is already a tradition that must be carried out in the community and as long as this does not conflict with aqidah and shari'ah then it is allowed by Islamic law Keywords: “uang asap” tradition, wedding traditions, maqasid shariah theory Daftar Pustaka Abu Ishaq al-Syatibi, Al-Muwafaqat fi Ushul al-Ahkam, Juz ke 2, Kairo: Dar al-Fikr, tt. Abu Malik Kamal bin Sayyid Salim, Sahih Fikih Sunnah, alih bahasa oleh: Khairul Amru Harahap, Faisal Saleh, Ed, Besus Hidayat Amin, Cet II , Jakarta: Pustaka Azzam, 2007. Abu Yasid, Fikih Keluarga, Jakarta: Erlangga, 2005. Abu Ishaq al-Syatibi, al-Muwafaqat fi ushul al-Syari’ah, ( Darul Ma’rifah, Beirut, 1997) Al Amin, Habibi. "Guardians Concept in Qur'an Perspective." Shakhsiyah Burhaniyah: Jurnal Penelitian Hukum Islam 6.1 (2021): 95-114. Al Amin, Habibi. "Guardians Concept in Qur'an Perspective." Shakhsiyah Burhaniyah: Jurnal Penelitian Hukum Islam 6.1 (2021): 95-114. Al Amin, Habibi. "Penciptaan Adam; Mendialogkan TafsiR Marah Labid dengan Teori Keadilan Gender." An-Nuha: Jurnal Kajian Islam, Pendidikan, Budaya Dan Sosial 1.1 (2014): 17-44. Al Amin, Habibi. "Penciptaan Adam; Mendialogkan TafsiR Marah Labid dengan Teori Keadilan Gender." An-Nuha: Jurnal Kajian Islam, Pendidikan, Budaya Dan Sosial 1.1 (2014): 17-44. Al Amin, Habibi. "Tafsir Sufi Lataâ€™ if al-Isyarat." SUHUF 9.1 (2016): 59-77. Al Amin, Habibi. "Tafsir Sufi Lataâ€™ if al-Isyarat." SUHUF 9.1 (2016): 59-77. Ali Qaim, Pernikahan Masalah Dan solusinya, Cet I, Jakarta: Cahya, 2009. Amir Syarifuddin, Ushul Fiqih, Cet 7, Jakarta: Kencana, 2014. Amir Syarifuddin, Ushul Fiqih, Cet 7, Jakarta: Kencana, 2014. Bambang Sunggono, Metodologi Penelitian Hukum, Jakarta: PT. Raja Grafindo Persada Cet. XIII, 2012. Departemen Pendidikan dan Kebudayaan, Kamus Besar Bahasa Indonesia, Ed. III Jakarta: Balai Pustaka, 2001. Dewi Wulansari, Hukum Adat Indonesia (suatu Pengantar), PT. Refika Aditama, Bandung, 2010. Fazlur Rahman, Islam, Ahsin Muhammad (Penrj.), Bandung: Pustaka, 1984. Hilman Hadikusuma, Hukum Perkawinan Adat dengan Adat Istiadat dan Upacara Adatnya, Bandung: PT. Citra Aditya Bakti, 2003. Ibnu Rusyd, Bidayatul Mujtahid Analisa Fiqih para Mujtahid, alih bahasa oleh: Imam Ghazali Said, Ahmad Zaidun, (Jakarta: Pustaka Amani, 2007), Jilid 2. Kajian Ilmiah FKI Ahla, Shuffah, Kamus Fiqih, Kediri: Lirboyo Press, 2016 Thahir Maloko. Dinamika Hukum Dalam Perkawinan, Cet. I; Makassar Alauddin University Press, 2012. Mahdi Ismail (tokoh agama), Wawancara kecamatan sungai pinyuh: juni 25-2017. Mohammad Daud Ali, Hukum Islam dan Peradilan Agama, Jakarta: PT RajaGrafindo Persada, 2002. Muliati Amin, Dakwah Jamaah (Disertasi) (Makassar: PPS. UIN Alauddin, 2010. Muttafaq Alah dari hadits Sahal- bin Sa’d dalam kish Al- Wahibah, Al- Bukhari (5087) (9/164), Muslim (4374) (5/215). Puna Siswa III aliyah ponpes liboyo, Esensi Pemikiran Mujtahid, All Rights Reserved, kediri 2003. Pusat Bahasa Departemen Pendidikan Nasional, Kamus Bahasa Indonesia, Jakarta:Pusat Bahasa, 2008. Nasution, Metode Naturalistik Kualitatif, Bandung: Tarsinto, 1996. Soemiati, Hukum Perkawinan Islam dan Undang-Undang Perkawinan, Liberty, Yogyakarta, 1892 Soerjo Wignjodipoero, Pengantar dan Asas-Asas Hukum Adat, PT. Toko Gunung Agung, Jakarta, 1983. Sugiyono, Metode penelitian pendidikan, ۤbandung: Alfabeta,2015. Sukanto, Meninjau Hukum Adat Indonesia: Suatu Pengantar Untuk Mempelajari Hukum Adat,Cet III Jakarta: PT RajaGrafindo Persada, 1996. Suwardi Endarsawara, Penelitian Kebudayaan:Idiologi, Epistimologi dan Aplikasi, Yogyakarta: Pustaka Widyatama, 2006 Syaikh al-‘Allamah Muhammad bin ‘Abdurrahman ad-Dimasyqi, Fiqih Empat Mazhab, Cet II, Bandung: Hasyimi Press, 2004. Syaikh Shalih bin Fauzan bin Abdullah Al- Fauzan, Ringkasan Fiqih Lengkap, Cet I, Jakarta: PT. Darul Falah, 2005. Taufiqurrahman, Zaky Fajar, and Habibi Al Amin. "Desain Pembelajaran Literasi Kitab Kuning Melalui Metode Sorogan dalam Meningkatkan Pemahaman Agama Islam." Syntax Literate; Jurnal Ilmiah Indonesia 6.2 (2021): 1467-1474. Taufiqurrahman, Zaky Fajar, and Habibi Al Amin. "Desain Pembelajaran Literasi Kitab Kuning Melalui Metode Sorogan dalam Meningkatkan Pemahaman Agama Islam." Syntax Literate; Jurnal Ilmiah Indonesia 6.2 (2021): 1467-1474.